On the Effect of Native SiO2 on Si over the SPR‐mediated Photocatalytic Activities of Au and Ag Nanoparticles. Issue 30 (19th May 2017) - Wang, Jiale; de Freitas, Isabel C.; Alves, Tiago V.; Ando, Romulo A.; Fang, Zebo; Camargo, Pedro H. C.
Abstract: In hybrid materials containing plasmonic nanoparticles such as Au and Ag, charge‐transfer processes from and to Au or Ag can affect both activities and selectivity in plasmonic catalysis. Inspired by the widespread utilization of commercial Si wafers in surface‐enhanced Raman spectroscopy (SERS) studies, we investigated herein the effect of the native SiO2 layer on Si wafers over the surface plasmon resonance (SPR)‐mediated activities of the Au and Ag nanoparticles (NPs). We prepared SERS‐active plasmonic comprised of Au and Ag NPs deposited onto a Si wafer. Here, two kinds of Si wafers were employed: Si with a native oxide surface layer (Si/SiO2 ) and Si without a native oxide surface layer (Si). This led to Si/SiO2 /Au, Si/SiO2 /Ag, Si/Au, and Si/Ag NPs. The SPR‐mediated oxidation of p ‐aminothiophenol (PATP) to p, p ′‐dimercaptoazobenzene (DMAB) was employed as a model transformation. By comparing the performances and band structures for the Si/Au and Si/Ag relative to Si/SiO2 /Au and Si/SiO2 /Ag NPs, it was found that the presence of a SiO2 layer was crucial to enable higher SPR‐mediated PATP to DMAB conversions. The SiO2 layer acts to prevent the charge transfer of SPR‐excited hot electrons from Au or Ag nanoparticles to the Si substrate. This enabled SPR‐excited hot electrons to be transferred to adsorbed O2 molecules, which then participate in the selective oxidation of PATP to DMAB. In the absence of a SiO2 layer, SPR‐excited hot electrons are preferentially transferred to Si instead of adsorbed O2 molecules, leading to much lower PATP oxidation. Abstract : Feeling the heat : The effect of the native SiO2 layer on Si wafer substrates was investigated towards the surface plasmon resonance (SPR)‐mediated photocatalytic oxidation activity of Au and Ag nanoparticles. The SiO2 layer was crucial to achieving higher conversions. It acted to prevent the charge transfer of SPR‐excited hot electrons from the nanoparticles to the Si substrate. This enabled the transfer of SPR‐excited hot electrons to adsorbed O2 that subsequently participates in the oxidation of p ‐aminothiophenol.